VERSTEHEN (PEMAHAMAN) TEKS SASTRA DALAM FILSAFAT TEORI PENGALAMAN - Winarsih, Suko (Jurnal Bahasa Lingua Scientia, 2014)
Literature is a noble work which can be interpreted phenomenological, interpretatively and hermeneutically. Phenomenology approach is done because literature has humanistic phenomena. Interpretation approach is done by the reader since the literature can be interpreted differently by the different readers. Hermeneutic approach is done since the literature contains certain culture.